Static Loading Simulation on Temporary Platform and Ladder Absorbent Chamber Design - Rinto Hindroyuwono; Rachmat Anggi Marvianto; Eliev Fajar Almaida; Yunus Bakhtiar Arafat (Sultan Publisher, 2024)
This study utilizes SolidWorks software to thoroughly examine the structural layout and static load simulation of a temporary platform and ladder in an adsorbent chamber. SolidWorks, a computer-aided design (CAD) and computer-aided engineering (CAE) software, offers robust tools for 3D modeling, simulation, and analysis, making it ideal for this type of structural assessment. Finite element analysis (FEA), a simulation model within SolidWorks, is employed to determine stress distribution and safety factors. The results demonstrate the platform's maximum stress at 198.65 MPa, below the yield strength of ASTM A36 Steel, leading to a safety factor of 1.3. These findings validate the design's safety and reliability for industrial use.